A symmetry-driven approach toward the total synthesis of dodecahedrane. (5th November 2022) - Chari, Jason V.; McDermott, Luca; Dander, Jacob E.; Simmons, Bryan J.; Garg, Neil K.
Abstract: Herein, we describe our progress toward the total synthesis of dodecahedrane, a complex and highly symmetrical hydrocarbon that bears twelve fused rings arranged in a cage-like architecture. Central to our approach is a late-stage [2+2+2+2+2] polyene cyclization cascade, which is expected to construct five new bonds and ten new rings in a single transformation. Toward this end, we describe efforts to synthesize key monomeric fragments, along with successful dimerization studies using a pinacol coupling approach. Subsequent studies include an attempted olefin metathesis rearrangement cascade in addition to a successful intramolecular photochemical [2+2] reaction. Although attempts to elaborate the photocycloaddition product were unsuccessful, our studies provide access to complex dimeric scaffolds and are expected to help guide our future total synthesis studies. Graphical abstract: Image 1